2018
DOI: 10.1002/1878-0261.12135
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL‐6‐JAK/Stat3 signaling in castration‐resistant prostate cancer cells enhances the NK cell‐mediated cytotoxicity via alteration of PD‐L1/NKG2D ligand levels

Abstract: To investigate whether IL‐6 signaling affects the susceptibility of castration‐resistant prostate cancer (CRPC) cells to cytotoxic action of natural killer (NK) cells, CRPC cell lines (having different IL‐6 levels) were developed by lentiviral transduction. While observing no secreted IL‐6 level in parental C4‐2 and CWR22Rv1 cells, we found the IL‐6 expression/secretion in these cells was induced after the transduction process and the IL‐6 level difference in C4‐2siIL‐6/sc and CWR22siIL‐6/sc cell CRPC cell set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 60 publications
4
81
1
1
Order By: Relevance
“…In this context, improving the NK cell‐mediated cytotoxicity, which is independent of tumor mutation burden and antigen presentation, may be an alternative immunotherapeutic approach to treat CRPC patients. In our previous in vitro and in vivo studies, we have demonstrated a significant antitumor NK cell activity toward PCa cells, supporting our hypothesis. Therefore, we speculate that discovering the adipocyte role in affecting CRPC cells and developing the resistance to NK cell cytotoxicity may be clinically important.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this context, improving the NK cell‐mediated cytotoxicity, which is independent of tumor mutation burden and antigen presentation, may be an alternative immunotherapeutic approach to treat CRPC patients. In our previous in vitro and in vivo studies, we have demonstrated a significant antitumor NK cell activity toward PCa cells, supporting our hypothesis. Therefore, we speculate that discovering the adipocyte role in affecting CRPC cells and developing the resistance to NK cell cytotoxicity may be clinically important.…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, we found JAK‐Stat3 signaling was critical signaling pathway that is responsible for the up‐regulation of PD‐L1/down‐regulation of NKG2D ligands in CRPC cells . We questioned whether this signaling pathway is also critical in triggering the adipocyte CM effect.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations